Biosorption of V(V) onto Lantana camara biochar modified by H3PO4: Characteristics, mechanism, and regenerative capacity. (March 2022) - Chen, Kexin; Ma, Danni; Yu, Haoyang; Zhang, Shan; Seyler, Barnabas C.; Chai, Zimo; Peng, Shuming
Abstract: Biochar has been widely recognized as an environmentally efficient adsorbent for removing heavy metals. However, considering the weak adsorption performance of the original biochar to the oxygen-containing anion, the adsorption of vanadium by biochar has rarely been investigated. This study proposes that H3 PO4 activated biochar made from an invasive plant species growing near mines is a novel material to be investigated for V(V) recovery and reuse. As a noxious, invasive plant, Lantana camara L. (LC) has become widely naturalized around the world. Biochar was prepared from LC by pyrolysis at different conditions (200 °C, 350 °C, 500 °C, and 650 °C). The adsorption effect of biochar with and without P pretreatment on V(V) in aqueous solution was compared. The results show that biochar prepared from LC impregnated with H3 PO4 (MLBC) had the highest adsorption capacity at 500 °C, and the maximal adsorption capacity fitted by Langmuir model was 77.38 mg g −1, which was considerably higher than that of untreated biochar (LBC, 5.89 mg g −1 ). The adsorption procedure was substantially fitted by the Langmuir isotherm and the pseudo-second-order kinetic. Additionally, the interaction of V(V) on MLBC is pH-dependent, and slightly acidic conditions are more favorable for adsorption. The characterization results indicated that electrostatic interaction, complexation reaction, and redox reaction were the primary mechanisms. After three cycles of adsorption, the final maximal adsorption capacity of MLBC remained at 76.03% of that of the virgin sample, demonstrating that MLBC had a recyclable capability to eliminate and restore V(V) from aqueous solutions. Graphical abstract: Image 1 Highlights: V(V) adsorption abilities of MLBC was 13.14 times that of LBC. Characterization analysis distinguished the adsorption mechanism of MLBC. Acidic conditions are favorable for MLBC to remove vanadate. The used MLBC can be easily isolated and displays significant reusability.